RECENT DIRECTIONS IN PRODUCTION AND OPERATION MANAGEMENT: A SURVEY - Modrak, Vladimir (International Journal of Industrial Engineering: Theory, Applications and Practice, 2016)
<!--[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!-- /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin-top:0cm; margin-right:0cm; margin-bottom:10.0pt; margin-left:0cm; text-align:justify; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-ansi-language:EN-US; mso-fareast-language:EN-US;} @page Section1 {size:612.0pt 792.0pt; margin:70.85pt 70.85pt 70.85pt 70.85pt; mso-header-margin:35.4pt; mso-footer-margin:35.4pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]-->Although the overviews on overall historical developments in given cognition domains are useful, in this survey a modern era of operations management is treated. This work starts with describing the development and current position of operation management in production sector. Subsequently, decisive development features of operations management are articulated and analyzed. Finally, in the paper, opportunities and challenges of a modern operations management for practitioners are discussed.